Intermediates of N‐Heterocyclic Carbene (NHC) Dimerization Probed in the Gas Phase by Ion Mobility Mass Spectrometry: C−H⋅⋅⋅:C Hydrogen Bonding Versus Covalent Dimer Formation. Issue 10 (17th January 2019) - Paul, Mathias; Detmar, Eric; Schlangen, Maria; Breugst, Martin; Neudörfl, Jörg‐Martin; Schwarz, Helmut; Berkessel, Albrecht; Schäfer, Mathias
Abstract: N‐Heterocyclic carbenes (NHCs, :C ) can interact with azolium salts (C−H + ) by either forming a hydrogen‐bonded aggregate (CHC + ) or a covalent C−C bond (CCH + ). In this study, the intramolecular NHC–azolium salt interactions of aromatic imidazolin‐2‐ylidenes and saturated imidazolidin‐2‐ylidenes have been investigated in the gas phase by traveling wave ion mobility mass spectrometry (TW IMS) and DFT calculations. The TW IMS experiments provided evidence for the formation of these important intermediates in the gas phase, and they identified the predominant aggregation mode (hydrogen bond vs. covalent C−C) as a function of the nature of the interacting carbene–azolium pairs. Abstract : Riding waves ! The intramolecular NHC–azolium salt interactions of aromatic imidazolin‐2‐ylidenes and saturated imidazolidin‐2‐ylidenes were investigated in the gas phase by traveling‐wave ion mobility spectrometry (TW IMS) and DFT calculations. Hydrogen‐bonded aggregates and covalent C−C‐bonded dimers of the N‐heterocyclic carbenes and their azolium counterparts were identified and characterized (see figure).